A polgárosodás törékeny váza – Városhálózatunk a századfordulón I. (Városhierarchia – vázlat, tényképekkel) - Beluszky, Pál (Tér és Társadalom, 1990)
The way of establishment of Kingdom in Hungary at about 1000 A. D. related Hungary to the socio-economic development of West-European region (adoption of western Christianity and western legal and state organizations, relations with papacy, "import" of experts–soldiers, clergymen, priests, monastic orders, etc.). By the l3th century, West-European type towns developed in Hungary as well. However, the country (similar to other nations of Eastern Europe) could not follow the processes speeding up at the turn of 15th-16th centuries and leading to and resulting in bourgeois development. In addition to this, the expansion of Osmanli Turk Empire also exerted far-reaching negative influences on the country (conquest of a large part of Hungary for 150 years, constant wars). Until the mid-19th century, Hungary was a feudal state, with slow pace of modernization. After driving the Turks out (1680s and 1690s), the urban network revived in Medieval form, and towns functioned as moderate market centers of small regions or small towns inhabited by craftsmen. Bourgeois development speeded up in the second third of the 19th century: feudalism was eliminated legally in 1848. While in Western Europe, towns were the heads and instructors of civil society, they did not become the pioneers of bourgeois development in Hungary: They had to catch up with bourgeois transformation and had to fitt out the frame obtained (or received). Our 19th-century urban development took place within the Austro-Hungarian Monarchy, in an agrarian country. In 1870, the proportion of farming population was close to 80%. This number decreased to 60% by 1910. Capitalist transformation of agriculture, commerce and transport of agricultural goods (the most important incentive of railroad construction in Hungary), their processing and the development of credit and insurance institutions were in the center of our economic development, and at the same time, these factors were the most important factors of our urban development. The other stimulating force of urban development was the need to develop civil adminístration for the centers. Our investigation shows the hierarchy of urban network developed by 1900. Urban hierarchy was determined by the quantity and differentiation of institutions representing urban basic functions ("central-place" functions) and by defining the hierarchical rank of these institutions. Determining the hierarchical level of some of our institutions is facilitated by frequency values ("dispersion values"). This value indicates the number of settlements where the institution in question operates: the rarer an institution is, the higher hierarchical levet it indicates. When reconstructing the situation in 1900, we found 6 hierarchical levels including Budapest. I. 1. Budapest II. 2. Regional centers (of complete value) 3. Regional centers (partial) III. 4. Developed county seats (of complete value) 5. Developed county seats (partial) IV. 6. Towns of county-seat level (of complete value) 7. Towns of county-seat level (partial) V. 8. Medium-level towns (of complete value) 9. Medium-level towns (partial) VI. 10. Small towns Our findings are shown in Figure I and the appendix. Nevertheless they prove that the changes in Hungarian urban network at the turn of 19th century are primarily the result of external factors and, above alt, state intervention. One of the basic means of this was to settle government and administrative functions. Thus a great number of small settlements without urban functions, urban society and significant bourgeoisie got urban institutions and got onto relatively high hierarchical levels. This special contradiction (high hierarchical rank–low levet of urbanization) characterized the majority of Hungarian towns and made them somewhat similar to East-European towns (lack of real bourgeoisie, dominance of civil servants, etc.). In Hungary, there were big differences among the circles of urban categories created on the basic of legal, functional and social terms (Fig. 3.). Manyfold, general urbanization was characteristic only of Budapest. At the turn of the century, the only bridgehead of modernization was Budapest, which – together with its outskirts – became a modern city with 1 million inhabitants.